2012
DOI: 10.1097/mpg.0b013e31824703c7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Anti‐deamidated Gliadin Peptide IgG Antibodies for Celiac Disease in Children and IgA‐deficient Patients

Abstract: The diagnostic performance of anti-dGp depends on the antibody isotype and on the age at CD diagnosis, anti-dGp IgG being a serological marker at least as useful as anti-tTG IgA for detecting CD in children ages 7 years or younger. Our data also indicate that anti-dGp IgG can improve the diagnosis of IgA-deficient patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 33 publications
(69 reference statements)
0
28
0
Order By: Relevance
“…What is the effectiveness of screening vs not screening for celiac disease in asymptomatic adults, adolescents, or children on morbidity, mortality, or quality of life? 20,23,39 Sensitivities and specificities were generally similar across age groups, with the exception of 1 study that reported specificity of 26% among persons 18 years or younger for the DGP IgA test. 20 Sensitivities were somewhat lower for adults than for children, but differences were slight.…”
Section: Key Questionsmentioning
confidence: 94%
“…What is the effectiveness of screening vs not screening for celiac disease in asymptomatic adults, adolescents, or children on morbidity, mortality, or quality of life? 20,23,39 Sensitivities and specificities were generally similar across age groups, with the exception of 1 study that reported specificity of 26% among persons 18 years or younger for the DGP IgA test. 20 Sensitivities were somewhat lower for adults than for children, but differences were slight.…”
Section: Key Questionsmentioning
confidence: 94%
“…At the moment, anti-TG2 antibodies form the most specific and sensitive marker for active celiac disease and their detection is the preferred diagnostic test in most cases [54,55]. New tests to detect IgG anti-gluten antibodies using synthetic deamidated gliadin peptides as substrates perform almost as well as the IgA anti-TG2 test [47] and have been shown to be especially useful in the diagnoses of infants and IgA-deficient patients [56].…”
Section: Antibody Response In Celiac Diseasementioning
confidence: 98%
“…Peptide gliadindetermination is a new technique for IgA deficient patients [30] [31]. CD is closely linked to the HLA region; the highest titles are set for the HLADQ2, while the remaining titles are for the DQ8 (Figure 1).…”
Section: Diagnosis Testmentioning
confidence: 99%